Once tesis sobre la cuestión nacional en España / Francesc Mercadé, Francesc Hernàndez y Benjamín Oltra - Hernández, Francesc (Hernández Hernández) Oltra, Benjamín; Mercadé, Francesc (Conciencia y libertad; 2)
Bibliografía: p. 145-154